2023
DOI: 10.1111/joim.13637
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 antibody dynamics over time and risk factors associated with infection and long COVID‐19 symptoms in large working environments

Abstract: Hansen CB, Dvoncova K, Pérez-Alós L, Fogh K, Madsen JR, Garred CH, et al. SARS-CoV-2 antibody dynamics over time and risk factors associated with infection and long COVID-19 symptoms in large working environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…A large cohort in Monaco also showed that hybrid immunity induces high levels of neutralizing antibody against SARS-CoV-2 [ 27 ]. Another study in Denmark which compared between fully BNT162b2 vaccinated individuals with and without previous SARS-CoV-2 infection also found that the proportion of individuals with high levels of total SARS-CoV-2 antibodies was significantly higher in those with prior infection (72.2%) than in infection-naïve individuals (35.4%), indicating robust humoral response induced by hybrid immunity [ 28 ]. In addition, a study from a large cohort in Sweden also showed hybrid immunity providing a high degree of protection against COVID-19 reinfection and hospitalisation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…A large cohort in Monaco also showed that hybrid immunity induces high levels of neutralizing antibody against SARS-CoV-2 [ 27 ]. Another study in Denmark which compared between fully BNT162b2 vaccinated individuals with and without previous SARS-CoV-2 infection also found that the proportion of individuals with high levels of total SARS-CoV-2 antibodies was significantly higher in those with prior infection (72.2%) than in infection-naïve individuals (35.4%), indicating robust humoral response induced by hybrid immunity [ 28 ]. In addition, a study from a large cohort in Sweden also showed hybrid immunity providing a high degree of protection against COVID-19 reinfection and hospitalisation [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ageusia was the strongest predictor of IgM seropositivity among the patients. Several studies across COVID-19 burden varying settings also reported the clinical utility of COVID-19 evocating clinical symptoms, or more specifically, fever, anosmia, and ageusia [ 15 , 17 , 18 , 20 , 21 , 45 , 47 ]. Ferreira et al .…”
Section: Discussionmentioning
confidence: 99%
“…In Bosnia and Herzegovina, Prguda-Mujic and colleagues reported a reduced risk of positive anti-SARS CoV-2 Ig levels in patients aged over 50 years old [30]. Other studies reported a reduced risk of SARS-CoV-2 positivity in younger individuals [16,45]. This could be due to the fact that elderly individuals are more aware of risks of COVID-19, and thus preventive methods could be more effectively implemented in them [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation